Constrained visualisation using Shepard-Bernoulli interpolation operator - CĂTINAȘ, Teodora (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
We consider Shepard-Bernoulli operator in order to solve a problem of interpolation of scattered data that is constrained to preserve positivity, using the technique described by K.W. Brodlie, M.R. Asim and K. Unsworth (2005). We also give some numerical examples. Mathematics Subject Classification (2010): 41A29, 41A05, 41A25, 41A35.